Polymer modified graphite material and preparation method and application thereof

By oxidation etching and reduction treatment on the graphite negative electrode material, porous graphite is prepared and an aromatic hydrocarbon polymer layer is formed on its surface, which solves the cycle stability of the graphite negative electrode material under fast charging and large-magnification conditions, and achieves excellent fast charging capability and cycle stability of the battery.

CN119170788BActive Publication Date: 2025-03-11CARBON ONE NEW ENERGY HANGZHOU CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411668269.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-11
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The existing graphite negative electrode materials have poor cycle stability under fast charging and large-scale conditions, and the rapid lithium embedded performance is limited, resulting in slow diffusion of lithium ions and electron leakage, affecting the rate performance and cycle life of the battery.

Method used

Porous graphite is prepared by oxidative etching and reduction treatment, and an aromatic hydrocarbon polymer layer containing only carbon, hydrogen and oxygen elements is formed on its surface to form a polymer-modified graphite material. Through the synergistic action of the porous structure and polymer layer, this material improves the diffusion channel and mobility of lithium ions, and enhances the rate performance and cycle stability of the battery.

Benefits of technology

It achieves excellent fast charging capability and cycle stability of the battery, improves the diffusion channel and mobility of lithium ions, and enhances the rate performance and structural stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to a polymer-modified graphite material and a preparation method and application thereof, wherein the polymer-modified graphite material comprises porous graphite and a polymer layer coated on at least part of the surface of the porous graphite, wherein the mass fraction of oxygen element on the surface of the porous graphite is 0.1%-1.5%, and the specific surface area of ​​the porous graphite is 2m 2 / g‑4m 2 / g, the average pore size of the porous graphite is 20nm-50nm, and the material of the polymer layer is an aromatic hydrocarbon polymer containing only carbon, hydrogen and oxygen elements. The polymer-modified graphite material can make the prepared battery have both excellent fast charging capability and cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of negative electrode materials, in particular to a polymer-modified graphite material and a preparation method and application thereof. Background Art

[0002] As the current mainstream negative electrode material, the fast lithium insertion performance of graphite negative electrode material largely determines the fast charging performance of lithium-ion batteries. Therefore, modifying the graphite negative electrode material is an effective way to improve the graphite lithium insertion behavior, such as carbon coating, element doping, oxidation etching, pore formation, etc. However, the above modification methods have limited effect on the rate improvement of graphite negative electrode materials, resulting in poor fast charging effect. At the same time, due to the native defects of the layer edge structure of graphite, the layered structure peeling caused by solvent co-intercalation, and the Li-ion electrolyte interface on the graphite / electrolyte interface. + -Li due to strong solvent interaction + Problems such as difficult desolvation, slow diffusion, and electrolyte reduction side reactions caused by electron leakage result in poor cycle stability of graphite negative electrode materials, especially under high-rate operating conditions, such as 6C charging, and long cycle life cannot be achieved. Summary of the Invention

[0003] Based on this, it is necessary to provide a polymer-modified graphite material and its preparation method and application to address the above problems. The polymer-modified graphite material can enable the prepared battery to have both excellent fast charging capability and cycle stability.

[0004] A polymer-modified graphite material comprising porous graphite and a polymer layer coated on at least a portion of the surface of the porous graphite, wherein the mass fraction of oxygen element on the surface of the porous graphite is 0.1%-1.5%, and the specific surface area of ​​the porous graphite is 2m 2 / g-4m 2 / g, the average pore diameter of the porous graphite is 20nm-50nm, and the material of the polymer layer is an aromatic hydrocarbon polymer containing only carbon, hydrogen and oxygen elements.

[0005] In one embodiment, the mass ratio of the porous graphite to the polymer layer is 100:(0.1-5).

[0006] In one embodiment, the thickness of the polymer layer is 0.01 nm-300 nm.

[0007] In one embodiment, the aromatic hydrocarbon polymer is selected from at least one of polyethylene glycol-polybutylene terephthalate, polyethylene glycol-polyethylene oxide-polybutylene terephthalate, and polyethylene glycol-polystyrene-polybutylene terephthalate.

[0008] In one embodiment, the median particle size of the porous graphite is 10 μm-18 μm.

[0009] In one embodiment, the polymer-modified graphite material satisfies at least one of the following conditions:

[0010] (1) The median particle size of the polymer-modified graphite material is 10 μm-18 μm;

[0011] (2) The specific surface area of ​​the polymer modified graphite material is 1m 2 / g-3m 2 / g.

[0012] The polymer modified graphite material of the present invention utilizes the rich porous structure of porous graphite to help increase lithium ion diffusion channels, shorten lithium ion diffusion paths, improve battery rate performance, and achieve fast charging. In addition, the specific surface area, average pore size, and surface oxygen content of the porous graphite are limited, which can further improve the battery rate performance and improve the battery cycle performance. At the same time, by setting an aromatic hydrocarbon polymer containing only carbon, hydrogen, and oxygen elements as the material of the polymer layer, on the one hand, the aromatic ring of the aromatic hydrocarbon polymer establishes a firm contact with the porous graphite surface through π-π interaction, and the aromatic ring can also effectively improve the The rigidity, thermal stability and mechanical strength of the polymer layer improve the structural stability of the battery; on the other hand, the lone pair electrons of the oxygen atoms in the aromatic hydrocarbon polymer chain coordinate with the lithium ions, reducing the migration energy barrier of the lithium ions, making it easier for them to dissociate from the polymer chain, accelerating the desolvation process, and improving the mobility and ionic conductivity of the lithium ions, thereby improving the ion transmission efficiency and rate performance of the battery, and further improving the fast charging performance; moreover, the hydrophilic groups in the polymer chain help to shorten the homogenization time and improve the slurry stability during the preparation of the negative electrode sheet, further improving the cycle stability of the battery.

[0013] Therefore, the polymer-modified graphite material of the present invention, under the synergistic effect of the specific porous graphite and polymer layer, can enable the prepared battery to have both excellent fast charging capability and cycle stability.

[0014] A method for preparing the polymer-modified graphite material as described above comprises the following steps:

[0015] Placing a graphite raw material in an oxygen-containing gas for oxidation etching to obtain prefabricated porous graphite, wherein the oxidation etching temperature is 400° C. to 1200° C., and the median particle size of the graphite raw material is 10 μm to 18 μm;

[0016] Placing the prefabricated porous graphite in a reducing atmosphere for reduction treatment to obtain porous graphite;

[0017] mixing an aromatic hydrocarbon polymer containing only carbon, hydrogen and oxygen elements, the porous graphite and water to obtain a slurry;

[0018] The slurry is spray-dried and then thermally cured to form a polymer layer, thereby obtaining a polymer-modified graphite material.

[0019] In one embodiment, in the step of placing the graphite raw material in an oxygen-containing gas for oxidation etching to obtain prefabricated porous graphite, at least one of the following conditions is met:

[0020] (1) The graphite raw material is selected from at least one of artificial graphite, natural graphite, and mesophase carbon microspheres;

[0021] (2) The oxygen-containing gas is selected from at least one of air, carbon dioxide, an oxygen-containing atmosphere, and water vapor, wherein the oxygen-containing atmosphere includes oxygen and an inert gas;

[0022] (3) The heating rate is 2℃ / min-10℃ / min, and the oxidation etching time is 30min-180min;

[0023] (4) The mass fraction of oxygen element on the surface of the prefabricated porous graphite is 4%-16%;

[0024] (5) The median particle size of the prefabricated porous graphite is 10 μm-18 μm.

[0025] In one embodiment, when the oxygen-containing gas is selected from a mixture of air and carbon dioxide, the volume ratio of the air to the carbon dioxide is 1:1-7:1, and the oxidation etching temperature is 700°C-1100°C.

[0026] In one embodiment, in the step of placing the prefabricated porous graphite in a reducing atmosphere for reduction treatment, at least one of the following conditions is met:

[0027] (1) The reducing atmosphere is selected from a hydrogen atmosphere and / or an inert gas atmosphere containing hydrogen, wherein the volume fraction of hydrogen in the inert gas atmosphere containing hydrogen is 5%-10%;

[0028] (2) The reduction temperature is 200℃-250℃, and the reduction time is 60min-360min.

[0029] In one embodiment, in the step of mixing the aromatic hydrocarbon polymer containing only carbon, hydrogen and oxygen elements, the porous graphite and water to obtain a slurry, at least one of the following conditions is met:

[0030] (1) The mass ratio of the porous graphite to the aromatic hydrocarbon polymer is 100:(0.1-5);

[0031] (2) The aromatic hydrocarbon polymer is selected from at least one of polyethylene glycol-polybutylene terephthalate, polyethylene glycol-polyethylene oxide-polybutylene terephthalate, and polyethylene glycol-polystyrene-polybutylene terephthalate;

[0032] (3) First, the aromatic hydrocarbon polymer and water are mixed, and then the porous graphite is added and mixed to obtain the slurry.

[0033] In one embodiment, in the step of spray drying the slurry, the inlet temperature of the spray drying is 220°C-300°C, and the outlet temperature is 100°C-120°C.

[0034] In one embodiment, in the step of forming the polymer layer by thermal curing, at least one of the following conditions is met:

[0035] (1) The thermal curing temperature is 140℃-200℃, and the thermal curing time is 1h-4h;

[0036] (2) After the polymer layer is formed by thermal curing, the process further includes demagnetization and screening to obtain a polymer-modified graphite material.

[0037] The preparation method of the polymer-modified graphite material of the present invention obtains porous graphite with a specific specific surface area, average pore size and specific surface oxygen content by adopting the method of oxidation etching and reduction of oxygen-containing gas. At the same time, a polymer layer is formed by spray drying and thermal curing to obtain a polymer-modified graphite material with excellent fast charging performance and cycle stability. The preparation method is simple and controllable and suitable for large-scale industrial production.

[0038] A negative electrode sheet comprises a current collector and a negative electrode active layer provided on the surface of the current collector, wherein the components of the negative electrode active layer include the polymer-modified graphite material as described above.

[0039] A secondary battery comprising the negative electrode sheet as described above. DETAILED DESCRIPTION

[0040] To facilitate understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the technical field of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments or embodiments and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, including any two related listed items, any more related listed items, or the combination of all related listed items.

[0042] The applicant has discovered through research that while the existing method of modifying the graphite surface to form a porous structure using oxidative etching can increase the rate of lithium ion insertion and enhance the battery's fast-charging performance, this method, while forming a porous structure, absorbs a large amount of oxygen on the graphite surface. Excessive oxygen content can lead to poor adhesion between the graphite and carbon or polymer coatings, resulting in poor coating effects. Furthermore, during battery use, the graphite is more likely to react with the electrolyte, reducing initial efficiency and affecting the battery's electrochemical performance.

[0043] To this end, the present invention provides a polymer-modified graphite material, which includes porous graphite and a polymer layer coated on at least a portion of the surface of the porous graphite, wherein the mass fraction of oxygen element on the surface of the porous graphite is 0.1%-1.5%, and the specific surface area of ​​the porous graphite is 2m 2 / g-4m 2 / g, the average pore diameter of the porous graphite is 20nm-50nm, and the material of the polymer layer is an aromatic hydrocarbon polymer containing only carbon, hydrogen and oxygen elements.

[0044] Specifically, the polymer-modified graphite material of the present invention adopts porous graphite as the main body, and utilizes the rich porous structure of porous graphite to help increase lithium ion diffusion channels, shorten lithium ion diffusion paths, improve battery rate performance, and achieve fast charging. In addition, the specific surface area, average pore size and surface oxygen content of the porous graphite are limited. Among them, under the synergistic effect of the specific surface area, average pore size and surface oxygen content, the rate performance of the battery can be further improved, while the cycle performance of the battery can be improved.

[0045] At the same time, an aromatic hydrocarbon polymer containing only carbon, hydrogen and oxygen elements is used as the material of the polymer layer to form a coating layer, which is used as an artificial SEI. On the one hand, the aromatic ring of the aromatic hydrocarbon polymer establishes a firm contact with the porous graphite surface through π-π interaction, and the aromatic ring can also effectively improve the rigidity, thermal stability and mechanical strength of the polymer layer, thereby improving the structural stability of the battery; on the other hand, the lone pair electrons of the oxygen atoms in the aromatic hydrocarbon polymer chain coordinate with the lithium ions, reducing the migration energy barrier of the lithium ions, making it easier for them to dissociate from the polymer chain, accelerating the desolvation process, and improving the mobility and ionic conductivity of the lithium ions, thereby improving the ion transfer efficiency and rate performance of the battery, and further improving the fast charging performance; moreover, the hydrophilic groups in the polymer chain help to shorten the homogenization time and improve the slurry stability during the preparation of the negative electrode sheet, further improving the cycle stability of the battery.

[0046] In addition, since the mass fraction of oxygen elements on the surface of porous graphite is 0.1%-1.5%, it can effectively improve the adhesion between the polymer layer and the porous graphite, further improve the firmness of the polymer layer on the porous graphite, improve the structural stability of the polymer-modified graphite material, and improve the cycle stability of the battery.

[0047] Therefore, the polymer-modified graphite material of the present invention, under the synergistic effect of the specific porous graphite and polymer layer, can enable the prepared battery to have both excellent fast charging capability and cycle stability.

[0048] Furthermore, in the present invention, the mass fraction of oxygen on the surface of the porous graphite is 0.1%-0.8%. Specifically, the mass fraction of oxygen on the surface of the porous graphite can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, or 0.8%. Such a configuration is conducive to improving the adhesion between the porous graphite and the polymer layer, and enhancing the structural stability of the polymer-modified graphite material.

[0049] It should be noted that, in the present invention, the mass fraction of oxygen element on the surface of porous graphite refers to the mass ratio of oxygen element contained on the surface of porous graphite, and the mass ratio is obtained by X-ray photoelectron spectrometry.

[0050] Furthermore, the polymer layer in the present invention can be coated partially or completely on the surface of the porous graphite, which can significantly improve the mobility and ionic conductivity of lithium ions, thereby improving the ion transport efficiency, rate performance, and cycling stability of the battery. Therefore, the present invention preferably has the polymer layer completely coated on the surface of the porous graphite.

[0051] Optionally, the average pore size of the porous graphite is 30 nm to 40 nm, specifically, the average pore size of the porous graphite can be 30 nm, 35 nm, or 40 nm. This configuration is beneficial for improving the rate performance of the polymer-modified graphite material.

[0052] Optionally, the mass ratio of the porous graphite to the polymer layer is 100:(0.1-5), preferably 100:(0.5-2). Specifically, the mass ratio of the porous graphite to the polymer layer can be 100:0.5, 100:0.6, 100:0.7, 100:0.8, 100:0.9, 100:1, 100:1.1, 100:1.2, 100:1.3, 100:1.4, 100:1.5, 100:1.6, 100:1.7, 100:1.8, 100:1.9, or 100:2. By adjusting the mass ratio of the porous graphite to the polymer layer, the rate performance and cycle performance of the battery can be improved.

[0053] Optionally, the thickness of the polymer layer is 0.01 nm-300 nm. Specifically, the thickness of the polymer layer can be 0.01 nm, 1 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, 220 nm, 250 nm, 280 nm, or 300 nm. This configuration is beneficial for improving the ion transport efficiency, rate performance, and cycle performance of the battery.

[0054] Optionally, the aromatic hydrocarbon polymer is selected from at least one of polyethylene glycol-polybutylene terephthalate (PEG-PBT), polyethylene glycol-polyethylene oxide-polybutylene terephthalate (PEG-PEO-PBT), and polyethylene glycol-polystyrene-polybutylene terephthalate (PEG-PS-PBT). This configuration is conducive to better improving the battery's ion transport efficiency, rate performance, and cycle performance.

[0055] Optionally, the median particle size of the porous graphite is 10 μm-18 μm, preferably 12 μm-15 μm. Specifically, the median particle size of the porous graphite can be 12 μm, 13 μm, 14 μm, or 15 μm. This configuration is conducive to better controlling the specific surface area of ​​the porous graphite and improving the cycle stability of the battery.

[0056] Optionally, the median particle size of the polymer-modified graphite material is 10 μm-18 μm; preferably 12 μm-15 μm. Specifically, the median particle size of the porous graphite can be 12 μm, 13 μm, 14 μm, or 15 μm. By regulating the median particle size of the polymer-modified graphite material, it is advantageous to control the specific surface area of ​​the polymer-modified graphite material to be 1 m 2 / g-3m 2 / g. It is understood that the specific surface area of ​​the polymer modified graphite material can be 1m 2 / g, 1.5m 2 / g, 2m 2 / g, 2.5m 2 / g、3m 2 This configuration is beneficial to improving the cycle stability of the battery by regulating the specific surface area of ​​the polymer-modified graphite material.

[0057] At the same time, the present invention also provides a method for preparing the polymer-modified graphite material as described above, comprising the following steps:

[0058] S1, placing the graphite raw material in a gas containing oxygen elements for oxidation etching treatment to obtain prefabricated porous graphite, wherein the oxidation etching temperature is 400℃-1200℃, and the median particle size of the graphite raw material is 10μm-18μm; it can be understood that the graphite raw material is subjected to oxidation etching treatment in a gas containing oxygen elements. During this process, carbon atoms are taken away in the form of CO and CO2, and the graphite surface is etched to form a large number of pore structures; at the same time, oxygen atoms are also attached to the graphite surface by adsorption, and by limiting the oxidation etching temperature, the median particle size of the graphite raw material is reduced, so that the porous graphite prepared subsequently has rich pores, and the specific surface area of ​​the porous graphite is 2m 2 / g-4m 2 / g, and the average pore size is 20nm-50nm.

[0059] Furthermore, the median particle size of the graphite raw material is 12 μm-15 μm, specifically, the median particle size of the graphite raw material can be 12 μm, 13 μm, 14 μm, or 15 μm. This configuration can better control the specific surface area of ​​the porous graphite.

[0060] Optionally, the graphite raw material is selected from at least one of artificial graphite, natural graphite, and mesocarbon microbeads, preferably artificial graphite.

[0061] Optionally, in step S1, the heating rate is 2°C / min-10°C / min, preferably 4°C / min-6°C / min. This setting is conducive to improving the oxidation etching effect of the graphite raw material and better controlling the average pore size of the subsequent porous graphite.

[0062] Optionally, the gas containing oxygen elements is selected from at least one of air, carbon dioxide, an oxygen-containing atmosphere, and water vapor.

[0063] It should be noted that in the present invention, the corresponding oxidation etching temperature can be selected according to different types of oxygen-containing gases to ensure the oxidation etching effect on the graphite raw material and obtain porous graphite with a porous structure and a high specific surface area.

[0064] Specifically, when the oxygen-containing gas is air, the oxidation etching temperature is 700-1000°C, preferably 800-900°C, and the oxidation etching time is 30-160 minutes, preferably 40-70 minutes. This configuration is conducive to improving the oxidation etching effect of the graphite raw material and better controlling the average pore size of the subsequent porous graphite.

[0065] When the oxygen-containing gas is selected from carbon dioxide, the oxidation etching temperature is 900° C.-1200° C., preferably 1000° C.-1100° C., and the oxidation etching time is 50 min-240 min, preferably 80 min-120 min.

[0066] When the oxygen-containing gas is selected from a mixed gas of air and carbon dioxide, the volume fraction of the air and the carbon dioxide is 1:1-7:1, preferably 3:1-5:1, the oxidation etching temperature is 700°C-1100°C, preferably 850°C-950°C, and the oxidation etching time is 30min-180min, preferably 40min-80min.

[0067] In the present invention, the oxygen-containing atmosphere includes oxygen and an inert gas, wherein the volume fraction of oxygen is 5%-20%. This configuration is beneficial for ensuring the oxidation etching effect while controlling the production cost.

[0068] When the oxygen-containing gas is selected from an oxygen-containing atmosphere, the oxidation etching temperature is 400° C.-700° C., preferably 500° C.-600° C., and the oxidation etching time is 20 min-120 min, preferably 30 min-50 min.

[0069] It is understandable that the oxidation etching temperature can be adjusted according to the oxygen content while being ensured to be within the range of 400° C.-700° C. In general, as the oxygen content increases, the oxidation etching temperature decreases accordingly.

[0070] When the oxygen-containing gas is water vapor, the oxidation etching temperature is 700° C.-900° C., preferably 750° C.-850° C., and the oxidation etching time is 30 min-150 min, preferably 40 min-70 min.

[0071] It should be noted that experiments have found that during oxidative etching, carbon dioxide has a lower reactivity with graphite, making the corrosion reaction easier to control. Therefore, it is easier to regulate the specific surface area of ​​the final product by controlling the reaction time or temperature, thereby obtaining porous graphite with better performance. Therefore, in the present invention, the oxygen-containing gas is preferably selected from carbon dioxide, or a mixture of air and carbon dioxide, wherein the volume fraction of the air and carbon dioxide is 1:1-7:1.

[0072] Optionally, the mass fraction of oxygen elements on the surface of the prefabricated porous graphite is 4%-16%; specifically, the mass fraction of oxygen elements on the surface of the prefabricated porous graphite can be 4%, 6%, 8%, 10%, 12%, 14%, or 16%.

[0073] Optionally, the median particle size of the prefabricated porous graphite is 10 μm-18 μm, which can control the median particle size of the porous graphite to be 10 μm-18 μm, and better control the specific surface area of ​​the porous graphite.

[0074] S2, placing the prefabricated porous graphite in a reducing atmosphere for reduction treatment to obtain porous graphite; it is understood that the reduction treatment can consume the oxides on the surface of the graphite and reduce the oxygen content on the surface of the graphite, so that the mass fraction of oxygen element on the surface of the prepared porous graphite is 0.1%-1.5%, and the specific surface area of ​​the porous graphite is 2m 2 / g-4m 2 / g, and the average pore diameter of the porous graphite is 20nm-50nm.

[0075] Optionally, the reducing atmosphere is selected from an inert gas atmosphere containing hydrogen, wherein the volume fraction of hydrogen in the inert gas atmosphere containing hydrogen is 5%-10%.

[0076] Furthermore, the reduction temperature is 200° C.-250° C., and the reduction time is 60 min-360 min.

[0077] In one embodiment, the inert gas is selected from at least one of He, Ne, Ar, and Kr.

[0078] With such a setting, the oxygen element on the surface of the porous graphite can be fully reduced, and the content of oxygen element on the surface of the porous graphite can be better controlled to be 0.1%-0.8%.

[0079] S3, mixing an aromatic hydrocarbon polymer containing only carbon, hydrogen and oxygen elements, the porous graphite and water to obtain a slurry.

[0080] Optionally, the mass ratio of the porous graphite to the aromatic hydrocarbon polymer is 100:(0.1-5), preferably 100:(0.5-2); such a setting is conducive to controlling the mass ratio of the porous graphite and the polymer layer, and better controlling the thickness of the polymer layer.

[0081] Optionally, the aromatic hydrocarbon polymer is selected from at least one of polyethylene glycol-polybutylene terephthalate (PEG-PBT), polyethylene glycol-polyethylene oxide-polybutylene terephthalate (PEG-PEO-PBT), and polyethylene glycol-polystyrene-polybutylene terephthalate (PEG-PS-PBT).

[0082] Optionally, in step S1, the aromatic hydrocarbon polymer and water are first mixed, and then the porous graphite is added and mixed to obtain the slurry.

[0083] Specifically, the aromatic hydrocarbon polymer and water are first mixed and stirred for 0.1 to 2 hours, preferably 0.5 to 1 hour. The porous graphite is then added and stirred for 0.5 to 3 hours, preferably 1 to 2 hours, to obtain the slurry. This arrangement allows for thorough mixing of the components, which helps ensure uniform dispersion of the slurry.

[0084] In one embodiment, the aromatic hydrocarbon polymer and water are mixed to obtain a mixed solution, wherein the solid content of the mixed solution is 5%-40%, preferably 15%-25%.

[0085] S4, spray drying the slurry, and then thermally curing it to form a polymer layer to obtain a polymer-modified graphite material.

[0086] Optionally, the inlet temperature of the spray drying is 220° C.-300° C., preferably 240° C.-260° C., and the outlet temperature is 100° C.-120° C., 105° C.-115° C. Such an arrangement is conducive to drying the slurry into spherical particles.

[0087] Optionally, the thermal curing temperature is 140° C.-200° C., preferably 160° C.-180° C., and the thermal curing time is 1 h-4 h, preferably 1.5 h-2 h. With such an arrangement, the polymer layer can be better formed and the coating effect can be improved.

[0088] Optionally, after the polymer layer is formed by thermal curing, demagnetization and screening are further performed to obtain a polymer-modified graphite material.

[0089] The demagnetization method may be an electromagnetic demagnetizer or a permanent magnet, and the electromagnetic demagnetizer is preferred.

[0090] In one embodiment, the mesh size of the sieve used in the screening is greater than or equal to 325 mesh, such as 325 mesh, 350 mesh, 400 mesh, etc. In this way, a polymer-modified graphite material with uniform particle size can be obtained.

[0091] The preparation method of the polymer-modified graphite material of the present invention obtains porous graphite with a specific specific surface area, average pore size and specific surface oxygen content by adopting the method of oxidation etching and reduction of oxygen-containing gas. At the same time, a polymer layer is formed by spray drying and thermal curing to obtain a polymer-modified graphite material with excellent fast charging performance and cycle stability. At the same time, the preparation method is simple and controllable, and is suitable for large-scale industrial production.

[0092] A negative electrode sheet comprises a current collector and a negative electrode active layer provided on the surface of the current collector, wherein the components of the negative electrode active layer include the polymer-modified graphite material as described above.

[0093] A secondary battery comprising the negative electrode sheet as described above.

[0094] In one embodiment, the secondary battery may be a lithium battery.

[0095] The polymer-modified graphite material, its preparation method, and its application are further described below through the following specific examples. However, those skilled in the art will understand that the following examples are merely illustrative of the present invention and should not be construed as limiting the scope of the present invention. Where specific conditions are not specified in the examples, the experiments were performed under conventional conditions or those recommended by the manufacturer. Reagents or instruments used, for which the manufacturer is not specified, are commercially available conventional products.

[0096] Example 1

[0097] Artificial graphite with a median particle size of approximately 13.5 μm is placed in an oxygen-containing gas for oxidation etching treatment to obtain prefabricated porous graphite, wherein the oxygen-containing gas is a mixed gas of air and carbon dioxide, the volume ratio of the air to the carbon dioxide is 4:1, the oxidation etching temperature is 900°C, the heating rate is 5°C / min, and the oxidation etching time is 60 min.

[0098] The prefabricated porous graphite obtained above is placed in a reducing atmosphere for reduction treatment to obtain porous graphite, wherein the reducing atmosphere is selected from an argon atmosphere containing hydrogen, wherein the volume fraction of hydrogen is 8%, the reduction temperature is 250° C., and the reduction time is 180 min.

[0099] Polyethylene glycol-polybutylene terephthalate (PEG-PBT) was mixed with purified water and stirred for 0.8 h. The porous graphite obtained above was added and stirred for 1.5 h to obtain a uniformly dispersed slurry; wherein the mass ratio of porous graphite to PEG-PBT was 100:1.

[0100] The slurry obtained above was spray-dried; by adjusting the heating power and feed rate, the inlet air temperature of the spray drying was controlled to be 250°C and the outlet air temperature was controlled to be 110°C, and then placed at 170°C for thermal curing for 1.8 hours to form a polymer layer, followed by demagnetization by an electromagnetic demagnetizer and finally sieved with a 325-mesh screen to obtain a polymer-modified graphite material.

[0101] According to the test, the polymer-modified graphite material prepared in this embodiment includes porous graphite, and polymer is formed on the surface of the porous graphite. At the same time, according to the test, the thickness of the polymer layer is about 116 nm.

[0102] Example 2

[0103] Artificial graphite with a median particle size of approximately 12.5 μm is placed in an oxygen-containing gas for oxidation etching treatment to obtain prefabricated porous graphite, wherein the oxygen-containing gas is a mixture of air and carbon dioxide, the volume ratio of the air to the carbon dioxide is 5:1, the oxidation etching temperature is 850°C, the heating rate is 4°C / min, and the oxidation etching time is 40 min.

[0104] The prefabricated porous graphite obtained above is placed in a reducing atmosphere for reduction treatment to obtain porous graphite, wherein the reducing atmosphere is selected from an argon atmosphere containing hydrogen, wherein the volume fraction of hydrogen is 5%, the reduction temperature is 200°C, and the reduction time is 120 minutes.

[0105] Polyethylene glycol-polybutylene terephthalate (PEG-PBT) was mixed with purified water and stirred for 0.5 h. The porous graphite obtained above was added and stirred for 1 h to obtain a uniformly dispersed slurry; wherein the mass ratio of porous graphite to PEG-PBT was 100:0.5.

[0106] The slurry obtained above was spray-dried; by adjusting the heating power and feed rate, the inlet air temperature of the spray drying was controlled to be 240°C and the outlet air temperature was controlled to be 105°C, and then placed at 160°C for thermal curing for 1.5 hours to form a polymer layer, followed by demagnetization by an electromagnetic demagnetizer and finally sieved with a 325-mesh screen to obtain a polymer-modified graphite material, wherein the thickness of the polymer layer was about 74 nm.

[0107] Example 3

[0108] Artificial graphite with a median particle size of approximately 14.5 μm is placed in an oxygen-containing gas for oxidation etching treatment to obtain prefabricated porous graphite, wherein the oxygen-containing gas is a mixture of air and carbon dioxide, the volume ratio of the air to the carbon dioxide is 3:1, the oxidation etching temperature is 950°C, the heating rate is 6°C / min, and the oxidation etching time is 80 min.

[0109] The prefabricated porous graphite obtained above is placed in a reducing atmosphere for reduction treatment to obtain porous graphite, wherein the reducing atmosphere is selected from an argon atmosphere containing hydrogen, wherein the volume fraction of hydrogen is 10%, the reduction temperature is 200°C, and the reduction time is 240 minutes.

[0110] Polyethylene glycol-polybutylene terephthalate (PEG-PBT) was mixed with purified water and stirred for 1 h. The porous graphite obtained above was added and stirred for another 2 h to obtain a uniformly dispersed slurry. The mass ratio of the porous graphite to the PEG-PBT was 100:2.

[0111] The slurry obtained above was spray-dried; by adjusting the heating power and feed rate, the inlet air temperature of the spray drying was controlled to 260°C and the outlet air temperature was controlled to 115°C, and then placed at 180°C for thermal curing for 2 hours to form a polymer layer, followed by demagnetization by an electromagnetic demagnetizer and finally sieved with a 325-mesh screen to obtain a polymer-modified graphite material, wherein the thickness of the polymer layer was about 189 nm.

[0112] Example 4

[0113] The only difference between Example 4 and Example 1 is that the oxidation etching time is 180 min, and the other conditions are the same, thereby obtaining a polymer-modified graphite material, wherein the thickness of the polymer layer is about 104 nm.

[0114] Example 5

[0115] The only difference between Example 5 and Example 1 is that the oxidation etching temperature is 700° C., and the other conditions are the same, thereby obtaining a polymer-modified graphite material, wherein the thickness of the polymer layer is about 101 nm.

[0116] Example 6

[0117] The only difference between Example 6 and Example 1 is that the reduction time is 60 min, and the other conditions are the same, thereby obtaining a polymer-modified graphite material, wherein the thickness of the polymer layer is about 95 nm.

[0118] Example 7

[0119] The only difference between Example 7 and Example 1 is that the mass ratio of porous graphite to PEG-PBT is 100:0.1, and the other conditions are the same, thereby obtaining a polymer-modified graphite material, wherein the thickness of the polymer layer is about 11 nm.

[0120] Example 8

[0121] The only difference between Example 8 and Example 1 is that the volume ratio of the air to the carbon dioxide is 1:1, and the other conditions are the same, thereby obtaining a polymer-modified graphite material, wherein the thickness of the polymer layer is about 119 nm.

[0122] Example 9

[0123] The only difference between Example 9 and Example 1 is that the oxygen-containing gas is air, the oxidation etching temperature is 850° C., and the other conditions are the same, thereby obtaining a polymer-modified graphite material, wherein the thickness of the polymer layer is about 125 nm.

[0124] Example 10

[0125] The only difference between Example 10 and Example 1 is that the oxygen-containing gas is carbon dioxide, the oxidation etching temperature is 1050° C., and the other conditions are the same, thereby obtaining a polymer-modified graphite material, wherein the thickness of the polymer layer is about 108 nm.

[0126] Example 11

[0127] The only difference between Example 11 and Example 1 is that the oxygen-containing gas is an oxygen-containing atmosphere, wherein the volume fraction of oxygen is 10%, the volume fraction of argon is 90%, the oxidation etching temperature is 550°C, and the other conditions are the same, thereby obtaining a polymer-modified graphite material, wherein the thickness of the polymer layer is approximately 131 nm.

[0128] Example 12

[0129] The only difference between Example 12 and Example 1 is that the oxygen-containing gas is water vapor, the oxidation etching temperature is 800° C., and the other conditions are the same, thereby obtaining a polymer-modified graphite material, wherein the thickness of the polymer layer is about 124 nm.

[0130] Example 13

[0131] The only difference between Example 13 and Example 1 is that polyethylene glycol-polyethylene oxide-polybutylene terephthalate is used instead of polyethylene glycol-polybutylene terephthalate. Other conditions are the same, and a polymer-modified graphite material is obtained, wherein the thickness of the polymer layer is about 119 nm.

[0132] Example 14

[0133] The only difference between Example 14 and Example 1 is that polyethylene glycol-polystyrene-polybutylene terephthalate is used instead of polyethylene glycol-polybutylene terephthalate. Other conditions are the same, and a polymer-modified graphite material is obtained, wherein the thickness of the polymer layer is about 128 nm.

[0134] Example 15

[0135] Compared with Example 1, Example 15 differs only in that the reducing atmosphere is selected from nitrogen atmosphere, the reduction temperature is 850°C, and the reduction time is 180 min. Other conditions are the same, and a polymer-modified graphite material is obtained, wherein the thickness of the polymer layer is about 86 nm.

[0136] Example 16

[0137] The only difference between Example 16 and Example 1 is that natural graphite is used instead of artificial graphite. Other conditions are the same, and a polymer-modified graphite material is obtained, wherein the thickness of the polymer layer is about 110 nm.

[0138] Comparative Example 1

[0139] Comparative Example 1 differs from Example 1 only in that the median particle size of the artificial graphite is about 5 μm, and other conditions are the same, thereby obtaining a polymer-modified graphite material, wherein the thickness of the polymer layer is about 110 nm.

[0140] Comparative Example 2

[0141] Comparative Example 2 is different from Example 1 only in that the median particle size of the artificial graphite is about 20 μm, and other conditions are the same, thereby obtaining a polymer-modified graphite material, wherein the thickness of the polymer layer is about 91 nm.

[0142] Comparative Example 3

[0143] The only difference between Comparative Example 3 and Example 1 is that the oxidation etching temperature is 1200° C., and the other conditions are the same, thereby obtaining a polymer-modified graphite material, wherein the thickness of the polymer layer is about 122 nm.

[0144] Comparative Example 4

[0145] The only difference between Comparative Example 4 and Example 1 is that the oxidation etching temperature is 300° C., and the other conditions are the same, thereby obtaining a polymer-modified graphite material, wherein the thickness of the polymer layer is about 89 nm.

[0146] Comparative Example 5

[0147] Comparative Example 5 differs from Example 1 only in that polypropylene glycol is used instead of polyethylene glycol-polybutylene terephthalate (PBTE). All other conditions remain the same, resulting in a polymer-modified graphite material. In this comparative example, because polypropylene glycol is used instead of PBTE, the polymer lacks aromatic rings to establish a strong contact with the porous graphite surface via π-π interactions. Consequently, the formed polymer cannot effectively composite with the porous graphite, resulting in an inability to detect the corresponding polymer layer.

[0148] Comparative Example 6

[0149] Comparative Example 6 is different from Example 1 only in that a 1:1 mixture of polyphthalocyanine iron and polyethylene glycol is used instead of polyethylene glycol-polybutylene terephthalate, and other conditions are the same to obtain a polymer-modified graphite material, wherein the thickness of the polymer layer is about 106 nm.

[0150] Comparative Example 7

[0151] The only difference between Comparative Example 7 and Example 1 is that it does not contain the step of forming a polymer layer. That is, the porous graphite obtained above and pure water are directly mixed and stirred for 2.3 hours to obtain a uniformly dispersed slurry. The other conditions are the same to obtain a modified graphite material.

[0152] Comparative Example 8

[0153] Comparative Example 8 differs from Example 1 only in that the reduction treatment step is omitted. Specifically, polyethylene glycol-polybutylene terephthalate (PEG-PBT) is mixed with purified water and stirred for 0.8 h. The prefabricated porous graphite obtained above is then added and stirred for 1.5 h to obtain a uniformly dispersed slurry. All other conditions remain the same, yielding a polymer-modified graphite material. In this comparative example, since the reduction is not performed in a reducing gas, the surface oxygen content of the prefabricated porous graphite is high, making it difficult to coat the polymer layer. Consequently, the π-π interaction between the aromatic rings in the polymer layer and the prefabricated porous graphite is poor, preventing secure coating and even causing detachment. Consequently, the corresponding polymer layer cannot be detected.

[0154] The oxygen content on the surface of the prefabricated porous graphite prepared in Examples 1 to 16 and Comparative Examples 1 to 6, Comparative Example 8, the oxygen content on the surface of the porous graphite obtained after reduction, the median particle size of the porous graphite, the average pore size of the porous graphite, the specific surface area of ​​the porous graphite, the median particle size of the polymer-modified graphite material, and the specific surface area of ​​the polymer-modified graphite material were tested, and the oxygen content on the surface of the prefabricated porous graphite prepared in Comparative Example 7, the oxygen content on the surface of the porous graphite obtained after reduction, the median particle size of the porous graphite, the average pore size of the porous graphite, the specific surface area of ​​the porous graphite, the median particle size of the modified graphite material, and the specific surface area of ​​the modified graphite material were tested. The test results are shown in Table 1. The specific testing method is as follows:

[0155] Median particle size: using particle size (D 50 ) Test instrument: Malvern, Master Size 3000 test;

[0156] Specific surface area: Specific surface area (SSA) test instrument: American Micrometer model: Tristar3030;

[0157] Oxygen content: obtained by X-ray photoelectron spectroscopy (XPS) testing.

[0158] Table 1

[0159]

[0160] At the same time, the dispersibility of the polymer-modified graphite materials prepared in Examples 1 to 16, Comparative Examples 1 to 6, Comparative Example 8, and the modified graphite material prepared in Comparative Example 7 in water was tested, and the specific testing method was as follows: 5 g of the test sample was dispersed in 100 mL of water at a temperature of 25 ° C., controlling other conditions to be the same, and comparing the time required for uniform dispersion in water and the start of sedimentation. The test results are shown in Table 2.

[0161] Table 2

[0162]

[0163] As can be seen from the data in Table 2, the polymer layer formed by the aromatic hydrocarbon polymer containing only carbon, hydrogen and oxygen elements, i.e., the artificial SEI, in the present invention can effectively improve the hydrophilic properties of the surface of the polymer-modified graphite material and significantly improve its dispersibility in water, which is conducive to the uniform dispersion of the polymer-modified graphite material in the subsequent slurry preparation process.

[0164] The polymer-modified graphite materials prepared in Examples 1 to 16, Comparative Examples 1 to 6, and Comparative Example 8, as well as the modified graphite material prepared in Comparative Example 7, were respectively used to prepare negative electrode sheets, and the corresponding negative electrode sheets were assembled into batteries. The batteries were then tested for capacity, rate performance, and cycle performance. The test results are shown in Table 3. The specific test methods are as follows:

[0165] 0.1C discharge specific capacity test steps: 1. Let stand for 5 hours; 2. Discharge at 0.05C to 0.005V; 3. Discharge at 0.05mA constant current to 0.005V; 4. Let stand for 5 minutes; 5. Discharge at 0.01mA constant current to 0.005V; 6. Let stand for 5 minutes; 7. Charge at 0.1C to 2V; 8. Let stand for 5 minutes.

[0166] 2C discharge specific capacity test steps: 1. Let stand for 5h; 2. Discharge at 0.05C to 0.005V; 3. Discharge at 0.05mA constant current to 0.005V; 4. Let stand for 5min; 5. Discharge at 0.01mA constant current to 0.005V; 6. Let stand for 5min; 7. Charge at 0.1C to 2V; 8. Let stand for 5min; 9. Discharge at 2C to 0.005V; 10. Let stand for 30min; 11. Discharge at 0.1C to 0.005V; 12. Let stand for 30min; 13. Discharge at 0.05C to 0.005V; 14. Let stand for 30min; 15. Charge at 2C to 2V.

[0167] 5C discharge specific capacity test steps: 1. Let stand for 5h; 2. Discharge at 0.05C to 0.005V; 3. Discharge at 0.05mA constant current to 0.005V; 4. Let stand for 5min; 5. Discharge at 0.01mA constant current to 0.005V; 6. Let stand for 5min; 7. Charge at 0.1C to 2V; 8. Let stand for 5min; 9. Discharge at 5C to 0.005V; 10. Let stand for 30min; 11. Discharge at 0.1C to 0.005V; 12. Let stand for 30min; 13. Discharge at 0.05C to 0.005V; 14. Let stand for 30min; 15. Charge at 5C to 2V.

[0168] 0.1C 500-cycle capacity retention test steps: Same as the 0.1C discharge specific capacity test steps, set the program to cycle 500 times and then cut off, and compare its capacity retention rate.

[0169] Data processing: Select 4 data with a range of less than 3mAh, remove the maximum and minimum values ​​and calculate the average.

[0170] Table 3

[0171]

[0172] Combining the data in Table 1 and Table 3, it can be seen that compared with Examples 1 to 3, in Example 9, the etching gas is air, and the etching degree is not as good as the mixed gas of air and carbon dioxide, the pore size and specific surface area are both larger, and the capacity retention rate of the polymer modified graphite material decreases; and when the etching gas is carbon dioxide in Example 10, the temperature required for etching is higher, the energy consumption is higher, but the etching effect is worse, the pore size is smaller than the optimal pore size, and the rate performance and cycle performance decrease. In Example 8, when the volume ratio of air and carbon dioxide is 1:1, the etching degree is better than that of carbon dioxide alone, but it does not reach the optimal effect; in Example 11, when the etching gas is oxygen, the etching degree is more uncontrollable, and the etched pore size is larger, the specific surface area is larger, and it is not friendly to the cycle performance; in Example 12, when the etching gas is water vapor, the control effect is better than that of air and oxygen-containing gas, and it is environmentally friendly, but water vapor etching has high equipment requirements and large investment. In Example 15, the prefabricated porous graphite was reduced at 850° C. in nitrogen, but the oxygen content after nitrogen reduction was still high, indicating that hydrogen reduction is more efficient and consumes less energy than nitrogen reduction.

[0173] At the same time, in Comparative Example 1, since the median particle size of the artificial graphite is outside the optional value range, the small particle size has a large specific surface area, and the irreversible capacity of the polymer-modified graphite material will also be larger, resulting in poor cycle performance of the polymer-modified graphite material, and a larger specific surface area will also adsorb more oxygen atoms on the surface, which is consistent with the oxygen content of the graphite; in Comparative Example 2, the median particle size of the graphite is too large, and the large particle size has a small specific surface area, which makes its dispersibility poor, and the large particles have a long path for lithium ion deintercalation during the charge and discharge process, which is not conducive to rate performance; In Example 3, the oxidation temperature of artificial graphite of normal particle size was too high, the degree of oxidation was large, and the average pore size and specific surface area after etching were larger, and its performance was similar to that of Comparative Example 1. In Comparative Example 4, the oxygen content on the surface of the prefabricated porous graphite and the porous graphite material was similar, both very low, proving that there was no oxidative etching effect at 300°C in an atmosphere with a volume ratio of air to carbon dioxide of 4:1. Moreover, the small pore size and small specific surface area of ​​the porous graphite material further demonstrated that the etching was unsuccessful, thereby affecting the rate performance of the polymer-modified graphite material. In Comparative Example 5, polypropylene glycol was used instead of polyethylene glycol-polybutylene terephthalate. The lack of aromatic rings in the polymer to establish a strong contact with the porous graphite surface through π-π interactions prevented the polymer from effectively compounding with the porous graphite. This can also be reflected in the fact that the specific surface area of ​​the polymer-modified graphite material is not significantly reduced relative to the specific surface area of ​​the porous graphite, which will affect the rate performance and cycle performance of the material. In comparative example 6, a 1:1 mixture of polyphthalocyanine iron and polyethylene glycol is used to replace polyethylene glycol-polybutylene terephthalate, and the iron content exceeds the standard, resulting in an increase in battery side reactions, thereby causing a self-discharge reaction and affecting safety performance. In comparative example 7, no polymer layer coating is performed, the specific surface area is large, and the homogenization speed and stability are reduced, and the rate performance and cycle performance deteriorate. In comparative example 8, reduction is not performed in a reducing gas, and the surface oxygen content of the prefabricated porous graphite is large, which is not conducive to polymer layer coating. At this time, the π-π effect between the aromatic ring in the polymer layer and the prefabricated porous graphite is poor, and it is impossible to firmly coat it, thereby affecting the cycle stability of the graphite-modified material.

[0174] Therefore, in the present invention, by adopting the method of oxidation etching and reduction of oxygen-containing gas, and limiting the oxidation etching temperature and the median particle size of the graphite raw material, porous graphite with a specific specific surface area, average pore size and specific surface oxygen content can be obtained. At the same time, a polymer layer is formed by spray drying and thermal curing. Under the synergistic effect of the specific porous graphite and the polymer layer, the polymer-modified graphite material of the present invention can enable the prepared battery to have both excellent fast charging capability and cycle stability.

[0175] The technical features of the above-mentioned embodiments can be combined arbitrarily. In order to make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0176] The above-described embodiments merely illustrate several implementations of the present invention, and while their descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the patent. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, all of which fall within the scope of protection of the present invention. Therefore, the scope of protection of the patent for this invention shall be determined by the appended claims.

Claims

1. A polymer-modified graphite material, characterized in that: The polymer-modified graphite material comprises porous graphite and a polymer layer coated on at least part of the surface of the porous graphite, wherein the mass fraction of oxygen element on the surface of the porous graphite is 0.1%-1.5%, and the specific surface area of ​​the porous graphite is 2m 2 / g-4m 2 / g, the average pore size of the porous graphite is 20nm-50nm, and the material of the polymer layer is an aromatic hydrocarbon polymer containing only carbon, hydrogen and oxygen elements.

2. The polymer-modified graphite material according to claim 1, characterized in that: The mass ratio of the porous graphite to the polymer layer is 100:(0.1-5).

3. The polymer-modified graphite material according to claim 1, characterized in that: The thickness of the polymer layer is 0.01 nm-300 nm.

4. The polymer-modified graphite material according to claim 1, characterized in that: The aromatic hydrocarbon polymer is at least one selected from polyethylene glycol-polybutylene terephthalate, polyethylene glycol-polyethylene oxide-polybutylene terephthalate, and polyethylene glycol-polystyrene-polybutylene terephthalate.

5. The polymer-modified graphite material according to claim 1, characterized in that: The median particle size of the porous graphite is 10 μm-18 μm.

6. The polymer-modified graphite material according to claim 1, characterized in that: The polymer-modified graphite material satisfies at least one of the following conditions: (1) The median particle size of the polymer-modified graphite material is 10 μm-18 μm; (2) The specific surface area of ​​the polymer modified graphite material is 1m 2 / g-3m 2 / g.

7. A method for preparing a polymer-modified graphite material according to any one of claims 1 to 6, characterized in that: The following steps are involved: Placing a graphite raw material in a gas containing oxygen elements for oxidation etching treatment to obtain prefabricated porous graphite, wherein the oxidation etching temperature is 400° C.-1200° C., and the median particle size of the graphite raw material is 10 μm-18 μm; Placing the prefabricated porous graphite in a reducing atmosphere for reduction treatment to obtain porous graphite; Mixing an aromatic hydrocarbon polymer containing only carbon, hydrogen and oxygen elements, the porous graphite and water to obtain a slurry; The slurry is spray-dried and then thermally cured to form a polymer layer, thereby obtaining a polymer-modified graphite material.

8. The method for preparing a polymer-modified graphite material according to claim 7, characterized in that: In the step of placing the graphite raw material in a gas containing oxygen element for oxidation etching to obtain prefabricated porous graphite, at least one of the following conditions is met: (1) The graphite raw material is selected from at least one of artificial graphite, natural graphite, and mesophase carbon microspheres; (2) The oxygen-containing gas is selected from at least one of carbon dioxide, an oxygen-containing atmosphere, and water vapor, wherein the oxygen-containing atmosphere is air; or, the oxygen-containing atmosphere includes oxygen and an inert gas, and the volume fraction of the oxygen is 5%-20%; (3) The heating rate is 2℃ / min-10℃ / min, and the oxidation etching time is 30min-180min; (4) The mass fraction of oxygen element on the surface of the prefabricated porous graphite is 4%-16%; (5) The median particle size of the prefabricated porous graphite is 10 μm-18 μm.

9. The method for preparing a polymer-modified graphite material according to claim 8, characterized in that: When the oxygen-containing gas is selected from a mixed gas of air and carbon dioxide, the volume ratio of the air to the carbon dioxide is 1:1-7:1, and the oxidation etching temperature is 700°C-1100°C.

10. The method for preparing a polymer-modified graphite material according to claim 7, characterized in that: In the step of placing the prefabricated porous graphite in a reducing atmosphere for reduction treatment, at least one of the following conditions is met: (1) The reducing atmosphere is selected from an inert gas atmosphere containing hydrogen, wherein the volume fraction of hydrogen in the inert gas atmosphere containing hydrogen is 5%-10%; (2) The reduction temperature is 200℃-250℃, and the reduction time is 60min-360min.

11. The method for preparing a polymer-modified graphite material according to claim 7, characterized in that: In the step of mixing the aromatic hydrocarbon polymer containing only carbon, hydrogen and oxygen elements, the porous graphite and water to obtain a slurry, at least one of the following conditions is met: (1) The mass ratio of the porous graphite to the aromatic hydrocarbon polymer is 100:(0.1-5); (2) The aromatic hydrocarbon polymer is at least one selected from polyethylene glycol-polybutylene terephthalate, polyethylene glycol-polyethylene oxide-polybutylene terephthalate, and polyethylene glycol-polystyrene-polybutylene terephthalate; (3) The aromatic hydrocarbon polymer and water are first mixed, and then the porous graphite is added and mixed to obtain the slurry.

12. The method for preparing a polymer-modified graphite material according to claim 7, characterized in that: In the step of spray drying the slurry, the inlet temperature of the spray drying is 220°C-300°C, and the outlet temperature is 100°C-120°C.

13. The method for preparing a polymer-modified graphite material according to claim 7, characterized in that: In the step of forming the polymer layer by thermal curing, at least one of the following conditions is met: (1) The thermal curing temperature is 140℃-200℃, and the thermal curing time is 1h-4h; (2) After the polymer layer is formed by thermal curing, the method further includes demagnetization and screening to obtain a polymer-modified graphite material.

14. A negative electrode sheet, characterized in that: The negative electrode sheet comprises a current collector and a negative electrode active layer disposed on a surface of the current collector, and a component of the negative electrode active layer comprises the polymer-modified graphite material according to any one of claims 1 to 6.

15. A secondary battery comprising the negative electrode sheet according to claim 14.

Citation Information

Patent Citations

  • Negative electrode material, negative electrode plate, secondary battery and electronic device

    CN117996076A

  • Artificial graphite negative electrode material for high-rate lithium ion battery and preparation method therefor

    WO2022121136A1